Molecular characterization of culturable and non-culturable bacteria from leaching pools with cyanide - Sernaque Aguilar, Yacory Anahis (2019)
In the present study, bacterial communities in soil and water samples, from artisanal leaching pools with cyanide, were characterized by dependent and independent culture analyzes. For the characterization of the culturable bacterial community, classical techniques of microbiology were used, until obtaining pure strains, which were identified at the molecular level. On the other hand, uncultured bacterial communities were characterized by next-generation sequencing of the 16S rRNA gene. The culturable bacterial community was mainly represented by the genera Pseudomonas, Bacillus and Acinetobacter; while the predominant uncultured communities, in soil samples, were the proteobacteria (12.91%), Firmicutes (11.32%), Actinobacteria (11.25%) and Bacteroidetes (10.16%). On the other hand, in water samples, the edges of Firmicutes (59.16%) and Actinobacteria (38.99%) predominated.